Ultimate Load and Postfailure Behaviour of Box-Section Beams Under Pure Bending - Kotełko, M. (Engineering Transactions, 1996)
In this work the load-carrying capacity and plastic collapse mechanisms of thin-walled, rectangular and trapezoidal box-section beams subject to pure bending are investigated. The postbuckling elastic analysis is carried out using the effective width approach while the plastic buckling load is evaluated using the total strain theory. The failure of the beam is assumed to be initiated by buckling in a flange so that the flange mechanism of failure is expected. The analysis of plastic collapse mechanisms is carried out using basic assumptions of the rigid-plastic theory. The true (kinematically permissible) plastic mechanisms are taken into consideration. Three different theoretical solutions concerning the plastic moment capacity at a yield line are taken into account. Corresponding formulae for plastic moment at yield lines situated both in flanges and webs of the thin-walled beam are evaluated. The energy method is used in order to evaluate the bending moment capacity in terms of rotation angle of a global plastic hinge. The total energy of plastic deformation absorbed during rotation of the global plastic hinge is formulated and the bending moment is derived from this formula. For both rectangular and trapezoidal cross-section beams the idealized geometry of a global plastic hinge is based on the results of experimental tests. In the case of elastic buckling, the ultimate bending moment is determined approximately at the intersection point of two curves representing the bending moment in terms of the rotation angle: the postbuckling curve based upon approximate nonlinear analysis and the post-failure curve derived from the collapse mechanism analysis. Bending moment - rotation angle diagrams based on numerical results of the theoretical analysis, are compared with graphs recorded during experimental four-point tests.